2016
DOI: 10.1093/mnras/stw2861
|View full text |Cite
|
Sign up to set email alerts
|

Chemical trends in the Galactic halo from APOGEE data

Abstract: The galaxy formation process in the Λ-Cold Dark Matter scenario can be constrained from the analysis of stars in the Milky Way's halo system. We examine the variation of chemical abundances in distant halo stars observed by the Apache Point Galactic Evolution Experiment (APOGEE), as a function of distance from the Galactic center (r) and iron abundance ([M/H]), in the range 5 r 30 kpc and −2.5 < [M/H] < 0.0. We perform a statistical analysis of the abundance ratios derived by the APOGEE pipeline (ASPCAP) and d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 59 publications
3
35
0
Order By: Relevance
“…Some of these stars have distance estimates, and can therefore be spatially identified with either the disk or the halo. Carollo et al 2007;de Jong et al 2010;Fernández-Alvar et al 2017), which agrees well with the metal-poor halo component identified in our sample. Also similar to our findings, metallicities of the inner halo extend to the solar value, even though these are the tail of the metallicity distribution (e.g., Allende Prieto et al 2006) and not an additional component that is visible in Figure 2.…”
Section: Previous Evidence For a Metal-rich Halosupporting
confidence: 89%
“…Some of these stars have distance estimates, and can therefore be spatially identified with either the disk or the halo. Carollo et al 2007;de Jong et al 2010;Fernández-Alvar et al 2017), which agrees well with the metal-poor halo component identified in our sample. Also similar to our findings, metallicities of the inner halo extend to the solar value, even though these are the tail of the metallicity distribution (e.g., Allende Prieto et al 2006) and not an additional component that is visible in Figure 2.…”
Section: Previous Evidence For a Metal-rich Halosupporting
confidence: 89%
“…Additionally, full space motions may help separate populations that have distinct kinematics but similar chemistry. The physical distribution of the MW stars in our defined populations will be aided by incorporating accurate distance measurements (an initial study of the distribution of metal-poor stars in APOGEE is given in Fernández-Alvar et al 2017a). Finally, the companion paper by (Fernández-Alvar et al 2017b, Paper II in this series), further explores the chemical evolution of the two distinct metal-poor LMg and HMg populations identified in APOGEE.…”
Section: Discussionmentioning
confidence: 99%
“…The variation in the assembly histories of MW-mass galaxies has been shown theoretically to then shape the chemical patterns of their stellar halos (Font et al 2006;Tissera et al 2013). Fernández-Alvar et al (2017a), using APOGEE data combined with distances, found that the innermost regions of the Galactic halo are dominated by stars with higher [α/Fe]ratios, but that dominance shifts to stars with lower [α/Fe]ratios at larger distances, at least for the moderately metal-poor regime probed by APOGEE (i.e., stars with…”
Section: Potential Originsmentioning
confidence: 99%
“…However, we're only looking at stars with [Fe/H] > -1.2. Therefore, we are comparing to the most metal-rich stars in the halo as the halo MDF is peaked at [Fe/H] ≃ -2.1 and [Fe/H] ≃ -1.5 (see e.g., Allende Prieto et al 2014;An et al 2015;Fernández-Alvar et al 2017). …”
Section: Implications For Halo Accretion Scenariosmentioning
confidence: 99%